Comparative study of spiral computed tomography compared with ultrasound in appendicitis in Iraq - Dr. Mazin Kauther Abdul Latif; Abduljabbar Jameel Asal; Tariq Abdulhameed Midhat (Genius Journals, 2022)
This study focusses to a Comparative study of spiral computed tomography compared with ultrasound in appendicitis, and patients were collected from different hospitals in Iraq. which consisted of 100 devided 2groups (first by US and second by CT) Thus, CT of the appendix plays an important role in diagnosis and should be used as soon as possible from the onset of the first clinical signs. The radiograph depends on the size of the lesion, the stage and extent of the process, the involvement of adjacent organs, and the development of concomitant complications. All this determines the nature of the clinical manifestations and the severity of the patient's condition. Knowing the capabilities of radiological diagnostic methods and their rational use in many cases solves the issue of choosing the necessary treatment methods and determines the outcome of the disease
Keywords: CT; US; BMI; Appendicitis